The Influence of School Supervisors’ Role, Teachers’ Work Commitment, and School Culture on Learning Quality: A Quantitative Study in Elementary Schools of Sluke District Rembang - Siti Khanifah; Ngasbun Egar; Ghufron Abdullah (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
The quality of learning is a key indicator of the success of education at the elementary school level. This study aims to analyze the influence of school supervisors' roles, teachers' work commitment, and school culture on the quality of learning, both partially and simultaneously. This research employed a quantitative approach with an ex post facto design. The population consisted of elementary school teachers in Sluke District, Rembang Regency, with a sample of 115 respondents selected through proportional random sampling. Data were collected using a Likert scale questionnaire that had been tested for validity and reliability. The data were analyzed using simple and multiple linear regression techniques. The results showed that: (1) the role of school supervisors had a significant influence on the quality of learning, contributing 78%; (2) teachers' work commitment had a significant effect on the quality of learning with a contribution of 73.2%; (3) school culture had a significant influence on learning quality with the highest contribution of 89%; and (4) simultaneously, the three independent variables significantly influenced the quality of learning with a combined contribution of 92%. These findings emphasize that improving the quality of learning requires an integrated and collaborative approach that unites effective supervisory practices, strong teacher commitment, and a positive school culture. The study contributes to educational management theory by providing empirical evidence on the combined impact of these three factors, while also offering practical implications for policy formulation and school leadership strategies to sustainably enhance learning outcomes in elementary education.